Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank (World Bank, Washington, DC, 2017)
The Palestinian people face an increasingly uncertain political environment, and an economy that is failing to generate the jobs and incomes that are needed to improve living standards. Restrictions on trade and the access to resources, along with a decade long blockade of Gaza have led to a continuing decline in the productive base of the economy – with the share of Gross Domestic Product (GDP) in manufacturing halved in the last twenty-five years. Unemployment is now approaching 30 percent on average, with youth unemployment in Gaza twice as high. Although 2016 witnessed an improvement from the economic recession of 2014 -driven by a surge in reconstruction activity in Gaza – this is not sustainable nor sufficient to raise per capita incomes of the Palestinians. Looking forward GDP growth is expected to hover around 3.3 percent leading to a near stagnation in per capita income. Further increases in unemployment are also expected.